The emerging terrestrial record of Aptian-Albian global change. (September 2015) - Ludvigson, G.A.; Joeckel, R.M.; Murphy, L.R.; Stockli, D.F.; González, L.A.; Suarez, C.A.; Kirkland, J.I.; Al-Suwaidi, A.
Abstract: The integration of terrestrial carbonate δ 13 C chemostratigraphy and radiometric dates is opening a new window into the continental paleoclimate dynamics of the major carbon cycle perturbations of the Aptian-Albian interval. Results published to date by many researchers clearly show that there was a tight temporal coupling between Aptian-Albian marine, atmospheric, and terrestrial carbon pools that now permits refined global chemostratigraphic and chronostratigraphic correlations on time scales of 10 6 years or less. This development opens new opportunities to explore the Aptian-Albian Earth system by incorporating continental climate change dynamics in a developing global synthesis. In this paper, we present new U–Pb and U–Th/He age dates on a late Albian volcanic ash deposit in a stratigraphic section that fills a previous gap in in the terrestrial δ 13 C record. Here we also present, for the first time, coordinated δ 13 Ccarbonate, δ 18 Ocarbonate, and δ 13 Corganic data from stacked successions of paleosols in Aptian-Albian terrestrial strata of the Cedar Mountain Formation of Utah, USA. From the whole of this record, the late Aptian C10 C-isotope feature is especially noteworthy as an interval of major global change. Coordinated carbonate and organic carbon isotope data from this interval suggest that this positive carbon isotope excursion (CIE) was related to a buildup of atmospheric pCO2 to a peak level of about 1200 ppmV over a period of several million years duration, above earlier Aptian baseline levels of about 1000 ppmV. The C10 interval was immediately preceded and followed by drawdowns in pCO2 to levels of about 800 ppmV, and the entirety of the Aptian-Albian record from the Cedar Mountain Formation suggests a long-term fall of pCO2 levels from about 1000 down to 600 ppmV. We suggest that the late Aptian buildup likely is related to submarine volcanic activity in the Kerguelen Large Igneous Province in the southern Indian Ocean. Strata of the C-10 C-isotope feature are also associated with sedimentary evidence for an aridification event in the leeward rain shadow of the Sevier Mountains. On the basis of diagenetic studies of dolomitized calcretes in this C10 interval, we calculate that the precipitation-evaporation deficit intensified to the extent that 35–50% of the shallow groundwater system was lost to the atmosphere through evaporation.